Implementasi Pendidikan Karakter 6 Tabiat Luhur dalam Pembentukan Moral di TK Nurul Firdaus Bekasi Barat - Tukino; Sri Watini; Roza Yenita (Indo Publishing, 2025)
This research was conducted to determine the implementation of character education of 6 noble qualities, namely honesty, trust, harmony, compactness, good cooperation and mujhid-muzhid in the formation of morals in early childhood at Nurul Firdaus Kindergarten West Bekasi and to find out the role of teachers, parents and obstacles in the implementation of character education of 6 noble qualities. The research method used is descriptive with a qualitative approach, in order to gain a comprehensive understanding of the implementation of character education of 6 noble qualities in early childhood. The data sources used are primary and secondary data sources. Data collection was carried out by interview, observation and documentation methods. The data analysis techniques used are data reduction, data presentation and verification. The results of the study show that the implementation of character education of 6 noble habits in the formation of early childhood morals in Nurul Firdaus Kindergarten West Bekasi is carried out with exemplary methods, discipline, habituation and a conducive atmosphere. The role of parents and teachers is very important in the process of implementing character education. Obstacles in the implementation of character education 6 noble qualities are the lack of parental cooperation in implementing character education at home as educators do in schools and environments that are less supportive through bad behavior imitated by childrenThe results of this study provide an important meaning for educational development, e specially related to the application of character education in early childhood.